An Air Jet Distortion Generation System - M. Sivapragasam; S. Ramamurthy; M. D. Deshpande; P. White (International Journal of Rotating Machinery)
An air jet distortion generation system is developed to simulate the distorted flow field ahead of gas turbine engines in ground test facility. The flow field of a system of four jets arranged circumferentially and issuing into a confined counterflow was studied experimentally and numerically. The total pressure distortion parameters were evaluated at the Aerodynamic Interface Plane (AIP) for several values of mass flow ratios. Since the total pressure loss distribution at the AIP is characteristically “V” shaped, the number of jets was increased to obtain total pressure distributions as required for gas turbine engine testing. With this understanding, a methodology has been developed to generate a target total pressure distortion pattern at the AIP. Turbulent flow computations are used to iteratively progress towards the target distribution. This methodology was demonstrated for a distortion flow pattern typical of use in gas turbine engine testing using twenty jets, which is a smaller number than reported in the literature. The procedure converges with a root-mean-square error of 3.836% and is able to reproduce the target pattern and other distortion parameters.